Experimental and theoretical investigation on conformational and spectroscopic properties of dimethyl dithiodiglycolate, [CH3OC(O)CH2S]2 - Juncal, Luciana Celeste (2017)
Dimethyl dithiodiglycolate (DTG), [CH3OC(O)CH2S]2, was synthetized by complete oxidation of methyl thioglycolate (MTG) with I2, and characterized by gas chromatography coupled with electron-impact mass spectrometry. Fifteen stable conformers were found with the B3LYP/6-31 + G* approximation, with calculated populations at ambient temperature higher than 1%. The IR and Raman spectra of liquid DTG were interpreted for the first time, in terms of equilibrium between four conformers. The UV–visible spectra of DTG in solutions of ethanol, isopropanol and acetonitrile present a low-intensity band around 230 nm, interpreted mainly as arising from n → π* transitions localized at the C[dbnd]O groups, according to the prediction of TD-DFT calculations.